2021
DOI: 10.1111/eth.13203
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion with a twist: Aquatic beetle walks upside down on the underside of the water's surface

Abstract: While animals generally move through the aquatic environment by propelling themselves through the water or walking on submerged substrates, some have evolved the unique capacity to move along the water–air interface. This is because cohesive forces between water molecules cause the surface to be in tension, providing a physical substrate that can be used for support and pushed against for horizontal movement. Herein, we report on the use of the underside of the water's surface for locomotion in an unidentified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Recently, a research team in Australia observed an unidentified beetle (most likely family Hydrophilidae) that was capable of walking upside-down on the underside of the water’s surface without penetrating the surface. The appearance of an air bubble on the abdomen of the beetle was visible but currently, the exact mechanisms of how the beetle is capable of this feat or what cuticular features are involved are unknown [ 112 ].…”
Section: Hydrophobic Cuticular Structures Found In Insectsmentioning
confidence: 99%
“…Recently, a research team in Australia observed an unidentified beetle (most likely family Hydrophilidae) that was capable of walking upside-down on the underside of the water’s surface without penetrating the surface. The appearance of an air bubble on the abdomen of the beetle was visible but currently, the exact mechanisms of how the beetle is capable of this feat or what cuticular features are involved are unknown [ 112 ].…”
Section: Hydrophobic Cuticular Structures Found In Insectsmentioning
confidence: 99%